EGID3 project: prior knowledge of future teachers in geometry - Seabra, Marcela (2022)
In this paper we intend to present and discuss knowledge about geometric concepts and procedures developed by students, future teachers, during their non-higher education path. The identification of this knowledge is made in the context of the research project "EGID3: Geometry teaching, investing in diagnosis, difficulties and challenges", developed in the context of the Geometry curricular unit of the Undergraduate Degree in Basic Education of a Portuguese higher education institution, involving the teacher (first author) and the students of her class in a reflexive and collaborative research context about their own professional practice. The project aims, among other objectives, (i) to investigate students' perceptions about Geometry and its teaching; and (ii) to verify the contribution of diagnostic assessment practices to the learning of Geometry. For the construction (or consolidation) of new learning it is crucial to build upon the knowledge that students have been previously developing, in order to enhance more significant learning. For a student to achieve significant learning, he needs to mobilise and restructure his previous knowledge in order to establish connections between what he has already mastered and the new content to be learned. The valorisation of a student's previous knowledge allows the teacher to map and elaborate planning strategies in order to take this knowledge into account. In this sense, the data collection involved, in the first lesson of the curricular unit, a questionnaire of ten questions of open nature, involving geometric concepts and procedures that the students had worked in their basic education. Subsequently, a content analysis of the answers was performed. The results reveal that there are concepts in which students feel more secure (geometric figure, rectangle). They also reveal that many of them use a not very rigorous language when communicating their ideas about some concepts and procedures (angle).